The double-peaked type Ic Supernova 2019cad: another SN~2005bf-like object - Gutiérrez, Claudia C. (2021)
Fil: Gutiérrez, Finnish Centre for Astronomy with ESO (FINCA), FI-20014 University of Turku, Finland.